MRI of the Lung (Diagnostic Imaging, 2018)
This book provides a comprehensive overview of how to use MRI for the imaging of lung disease. Special emphasis is placed on routine applications and the clinical impact of MRI in each setting. In addition, current technological developments are reviewed and information presented on dedicated applications of MRI in preclinical and translational research, clinical trials, and specialized institutions. During the past two decades, significant advances in the technology have enabled MRI to enter and mature in the clinical arena of chest imaging. Standard protocols are now readily available on MR scanners, and MRI is recommended as the first- or second-line imaging modality for a variety of lung diseases, not limited to cystic fibrosis, pulmonary hypertension, and lung cancer. The benefits and added value of MRI originate from its ability to both visualize lung structure and provide information on different aspects of lung function, such as perfusion, respiratory motion, ventilation, and gas exchange. On this basis, novel quantitative surrogates for lung function and therapy control (imaging biomarkers) are generated. The second edition of MRI of the Lung has been fully updated to take account of recent advances. It is written by an internationally balanced team of renowned authors representing all major groups in the field.